High prevalence of human T‐cell leukemia virus type‐1b genotype among blood donors in Gabon, Central Africa - (:unkn) unknown (My University, 2020)
BACKGROUNDThe African continent is considered to be the largest endemic area of HTLV‐1 infection, with at least several million infected individuals. Systematic screening of blood donors can prevent the transmission of HTLV‐1 in blood. Gabon is one of the countries with the highest prevalence of HTLV‐1 worldwide, and yet the routine testing of blood donors has still not been introduced.METHODSAll blood donations collected between April and July 2017 at the Centre National de Transfusion Sanguine of Gabon were studied. Plasma samples were screened by ELISA for the presence of HTLV‐1/2 antibodies. Western blot (WB) and polymerase chain reaction (PCR) tests were used for confirmation.RESULTSIn total, 3123 blood donors were tested, including 1740 repeat and 1378 first‐time blood donors (FTBDs). Of them, 132 samples tested positive for HTLV‐1/2 by ELISA (4.2%). WB and PCR confirmed HTLV‐1 infection for 23 individuals. The overall prevalence of HTLV‐1 was 0.74% [95% CI 0.47%‐1.10%], 1% in FTBD, and 0.5% in repeat donors. Age and sex‐adjusted prevalence was five‐fold lower in FTBD than in the general adult population of rural areas of Gabon. All detected HTLV‐1 strains belonged to the central African HTLV‐1b genotype but were highly diverse.CONCLUSIONWe report an overall prevalence of HTLV‐1 of 0.74%, one of the highest values reported for blood donors in Africa. Given the high risk of HTLV‐1 transmission in blood, it is necessary to conduct cost‐effectiveness studies to determine the need and feasibility of implementing screening of HTLV‐1 in blood donors in Gabon.
Keywords: African Research